A Descriptive Study to Assess Attachment Styles, and Emotional Stability in Relation to Marital Satisfaction among Couples Residing in Selected Residential Areas of Gurugram, Haryana - Kumari, Kavita; Shaiju, Bindu; Aniyan, Asha (Journal of Advanced Research in Psychology & Psychotherapy (E-ISSN: 2581-5822), 2021)
Background: Marriage is one of the main decisions that an individual make in their life. Marital satisfaction constitutes the main determinant of life. There are several factors which predict marital satisfaction among couple like their attachment styles, emotional stability and demographic variables.Objective: To assess attachment styles, emotional stability of married couples, to seek relationship between marital satisfaction with their attachment styles and emotional stability and to seek relationship of marital satisfaction with selected demographic variables.Material and Method: A descriptive research design including 50 married couples via purposive sampling. Tools used were- For Attachment styles -Adult attachment scale, For marital satisfaction-ENRICH marital satisfaction scale, For emotional stability-Schutte Self Report Emotional Intelligence Test . Analysis and interpretation was done through SPSS version 16.0.Result: The findings revealed that out of 50 subjects, maximum 80% had Secure attachment style, maximum 100% male and 98% females were emotionally stable and maximum 96% males and 94% females had moderate marital satisfaction.All attachment styles and emotional stability had non significant positive relationship with marital satisfaction. Regarding demographic variables all had non significant relationship with marital satisfaction except age and family income.Conclusion: The study concluded that majority of married couples had moderate marital satisfaction and attachment style and emotional stability are predictors of marital satisfaction among married couples.How to cite this article:Kumari K. A Descriptive Study to Assess Attachment Styles, and Emotional Stability in Relation to Marital Satisfaction among Couples Residing in Selected Residential Areas of Gurugram, Haryana. J Adv Res Psychol Psychother 2020; 3(3&4): 1-7.DOI: https://doi.org/10.24321/2581.5822.202007